STANDAR OPERASIONAL PROSEDUR (SOP) SISTEM PELAPORAN KINERJA SDM PADA PROYEK DESAIN ARSITEKTUR DALAM KAITANNYA DENGAN DISIPLIN KERJA - Moh Saiful Hakiki; Tisa Angelia; Clara Sarti Widiwati (Program Studi Arsitektur Institut Teknologi Nasional (ITN) Malang, 2022)
As part of Architecture, Engineering & Construction (AEC), architectural design projects are carried out by an architectural design studio consulting firm, where within the company there is a design team consisting of human resources with expertise in design and project administration. The architectural design project is part of the Initiating and Planning process in the AEC project. In the framework of the Monitoring & Controlling process, tools are needed in the form of Standard Operating Procedures in the form of steps and documents where assessment and reporting can be carried out properly. Method of creating SOP is to use a Flowchart, so that will be a concise and easy-to-understand flow can be made, so that analysis and evaluation can then be carried out based on the sequence of steps of a series of process activities. Several conclusions obtained from this study: previous research shows that work discipline has an influence on employee performance; the performance aspects assessed by members of the design team are the quantity of work (project scope), time to do the task, and quality of work (conformity with company quality standards); aspects of work discipline that are assessed by team members, namely discipline in working hours regulations, discipline in dress and behavior etiquette, discipline in interacting and coordinating with other work units, and discipline in following regulations; performance appraisal is carried out by a superior in the design department (principal architect), while the work discipline assessment is carried out by a supervisor from the HR development department.